Efeitos da manipulação da regra do drible no desempenho e comportamento tático de jovens jogadores de basquetebol durante a realização de pequenos jogos 3x3 - Tomaz Lemos Nascimento Rosso (2022)
The manipulation of formats in small-sided games (SSG) have attracted great attention from researchers in the sports training field. The possibility of promoting technical, tactical and physical training simultaneously, the greater involvement and motivation of the players and, also, the perspective of emphasizing specific contents, highlight this training method. Few studies have focused on the effects of the SSG without dribble in basketball, which is a common strategy in the practice of training in this sport. These studies verified the impact on technical, physical and physiological variables, and SSG without dribble promote an increase in physiological responses and in the number of passes. On the other hand, no study has verified the consequences of manipulating the dribble rule on technical-tactical performance (effectiveness of actions and quality of decision-making) and tactical behavior (type of actions used to create scoring opportunities). The aim of this study was to verify the effects of dribble manipulation in regular 3x3 SSG, with dribble limitation and without dribble on the behavior of players based on the space creation dynamics (SCD) and on performance through the assessment instrument of basketball individual technical-tactical performance (AIP) for the U-16 category players. Eighteen U-16 players who competed at national level participated in the study. A pilot study was developed to calculate the sample size and to define the number of dribble limitation would be applied in the main study. There were 36 SSG in the main study, 12 regular, 12 limited to two dribbles and 12 without dribble. They lasted 4 minutes, with a 4-minute break, in random order and in a reduced half court (8.4x15m). Tactical behavior was evaluated using the SCD instrument and technical-tactical performance using the AIP. Analysis was conducted using a descriptive analysis (mean, standard deviation and relative and absolute frequencies), GEE analysis (General Estimated Equations – p≤0.05) and effect size calculation using Cramer's V. SPSS 20.0 software was used to perform the GEE and Excel program to calculate the effect size. The results showed that SSG without dribble offers more opportunities for attackers' without the ball behavior and for passing performance. Furthermore, the limitation of dribble provides opportunities for player behavior with and without the ball and for performance in passes and shots. On the other hand, the regular SSG presents more chances for individual behavior with the ball. In summary, the manipulation of the dribble rule impacted the use of tactical behaviors related to individual or group actions, as well as the technical-tactical performance (efficacy and decision making) of the U-16 basketball players who participated in that study.